'A Slap on the Wrist'? The Conservative Agenda in Queensland, Australia. (August 2015) - Hutchinson, Terry
Recent amendments to youth justice legislation in Queensland include opening Children's Court proceedings, removing the Principle of Detention as a Last Resort, facilitating transfers of 17 year-old offenders to adult prisons, instigating new bail offences, and introducing mandatory boot camp orders. This article examines the context of these changes including the inadequacies of the public policy process, and the impassioned political rhetoric imbued with simplistic slogans. This is a case study of regressive youth justice policy and the article reflects on the many causes underlying the reactive winding back of reform.